1988
DOI: 10.1126/science.3285468
|View full text |Cite
|
Sign up to set email alerts
|

Essential Fatty Acid Depletion of Renal Allografts and Prevention of Rejection

Abstract: A central hypothesis in transplantation biology is that resident leukocytes expressing class II histocompatibility antigens may determine the immunogenicity of an organ. By means of a novel method to deplete the kidney of resident leukocytes, essential fatty acid deficiency (EFAD), this hypothesis was tested in an intact, vascular organ. Kidneys subjected to EFAD and thus depleted of resident Ia-positive macrophages survived and functioned when transplanted across a major histocompatibility antigen barrier in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…EFAD also prolongs survival of transplanted incompatible kidneys and reduces autoimmune nephritis manifestations and myocardial infarction size (8,35,36). Although not studied specifically in those in vivo models, endothelial cells of an EFAD organism conceivably may show EFAD characteristics and may interact differently with emigrating leukocytes.…”
Section: Resultsmentioning
confidence: 99%
“…EFAD also prolongs survival of transplanted incompatible kidneys and reduces autoimmune nephritis manifestations and myocardial infarction size (8,35,36). Although not studied specifically in those in vivo models, endothelial cells of an EFAD organism conceivably may show EFAD characteristics and may interact differently with emigrating leukocytes.…”
Section: Resultsmentioning
confidence: 99%
“…56 Omega-3 fatty acids are postulated to exert their immunomodulatory effect by multiple mechanisms: inhibiting the effect of interleukin (IL)-1, tumour necrosis factor, altering histocompatability antigen (HLA-DR) expression, reducing vascular smooth muscle proliferation, and vascular permeability. 57 Reports have suggested that the administration of omega-3 fatty acids in the form of fish oil have improved renal haemodynamics and serum lipids in recipients of renal transplants. Furthermore, patients taking supplemental fish oil had better control of post-transplant hypertension, with fewer acute and chronic rejection episodes.58-68 However, most of these studies have been small and limited to a single centre.…”
Section: Effect Of Dietary Supplementation With Fish Oil On Serum Lipidsmentioning
confidence: 99%
“…Their activities and properties are regulated by various cytokines and by fatty acid-derived messenger molecules (Schreiner et al 1988;Luft et al 2002;Morelli & Thomson, 2003). Prostaglandins and leukotrienes are mostly short-lived molecules acting in an autocrine or paracrine mode.…”
mentioning
confidence: 99%